Withaferin A ameliorates ovarian cancer-induced cachexia and proinflammatory signaling - Alex R. Straughn; Sham S. Kakar (BMC, 2019)
Abstract Background Ovarian cancer is the fifth leading cause of cancer-related deaths amongst women in the United States. Cachexia is the primary cause of death in approximately 30% of cancer patients, and is often evidenced in ovarian cancer patients. We tested the steroidal lactone Withaferin A to examine if it could ameliorate ovarian cancer-induced cachexia. Methods Six-week-old severely immunodeficient female mice were xenografted with the ovarian cancer cell line A2780 followed by treatment with Withaferin A or vehicle. Changes in functional grip strength were assessed on a weekly basis. Postmortem, H&E staining was performed on skeletal muscle sections and immunofluorescent immunohistochemistry was performed on skeletal muscle and tumor sections. The levels of NF-κB-related proinflammatory cytokines were assessed in the xenografted tumors and in resident host skeletal muscle. Results Xenografting of the A2780 cell line resulted in a significant rate of mortality, which was attenuated by a therapeutic dosage of Withaferin A. Mice that received vehicle treatment following xenografting exhibited functional muscle decline over the course of the study. The therapeutic dosage Withaferin A treatment attenuated this reduction in grip strength, whereas the supratherapeutic dosage of Withaferin A was found to be toxic/lethal and demonstrated a further decline in functional muscle strength and an increased rate of mortality on par with vehicle treatment. At a histological level, the vehicle treated tumor-bearing mice exhibited a profound reduction in myofibrillar cross-sectional area compared to the vehicle treated tumor-free control group. The atrophic changes induced by the xenografted tumor were significantly ameliorated by treatment with Withaferin A. The combination of functional muscle weakening and induction of myofibrillar atrophy corroborate a cachectic phenotype, which was functionally rescued by Withaferin A. Further, treatment completely abolished the slow-to-fast myofiber type conversion observed in the settings of cancer-induced cachexia. In both host resident skeletal muscle and the xenografted tumors, we report an increase in NF-κB-related proinflammatory cytokines that was reversed by Withaferin A treatment. Finally, we demonstrated that Withaferin A significantly downregulates cytosolic and nuclear levels of phospho-p65, the active canonical NF-κB transcription factor, in xenografted tumors. Conclusions Cumulatively, our results demonstrate a previously overlooked role of Withaferin A in a xenograft model of ovarian cancer. We propose mechanisms by which Withaferin A reduces NF-κB-dependent pro-inflammatory cytokine production leading to an attenuation of the cachectic phenotype in an i.p. xenograft model of ovarian cancer.